A cortico-cerebellar loop for motor planning. (1st November 2018) - Gao, Zhenyu; Davis, Courtney; Thomas, Alyse; Economo, Michael; Abrego, Amada; Svoboda, Karel; Zeeuw, Chris; Li, Nuo
Abstract Persistent and ramping neural activity in the frontal cortex anticipates specific movements1–6 . Preparatory activity is distributed across several brain regions7, 8, but it is unclear which brain areas are involved and how this activity is mediated by multi-regional interactions. The cerebellum is thought to be primarily involved in the short-timescale control of movement9–12 ; however, roles for this structure in cognitive processes have also been proposed13–16 . In humans, cerebellar damage can cause defects in planning and working memory13 . Here we show that persistent representation of information in the frontal cortex during motor planning is dependent on the cerebellum. Mice performed a sensory discrimination task in which they used short-term memory to plan a future directional movement. A transient perturbation in the medial deep cerebellar nucleus (fastigial nucleus) disrupted subsequent correct responses without hampering movement execution. Preparatory activity was observed in both the frontal cortex and the cerebellar nuclei, seconds before the onset of movement. The silencing of frontal cortex activity abolished preparatory activity in the cerebellar nuclei, and fastigial activity was necessary to maintain cortical preparatory activity. Fastigial output selectively targeted the behaviourally relevant part of the frontal cortex through the thalamus, thus closing a cortico-cerebellar loop. Our results support the view that persistent neural dynamics during motor planning is maintained by neural circuits that span multiple brain regions17, and that cerebellar computations extend beyond online motor control13–15, 18 . The cerebellum is critical for the coding of future movement in the frontal cortex.